Love, Anarchy and Emma Goldman : a biography - Falk, Candace (New York : Holt, Rinehart & Winston, 1984)
With marvelous clarity and depth, Candace Falk illuminates for us an Emma Goldman shaped by her time yet presaging in her life the situation and conflicts of women in our time. One of the most famous political activists of all time, Emma Goldman was also infamous for her radical anarchist views and her "scandalous" personal life. In public, Goldman was a firebrand, confidently agitating for labor reform, anarchism, birth control, and women's independence. But behind closed doors she was more vulnerable, especially when it came to the love of her life. Love, Anarchy, & Emma Goldman is an account of Goldman's legendary career as a political activist. But it is more than that--it is the only biography of Emma Goldman. The flow of her life and words is at its core. Here, Candace Falk offers an intimate look at how Goldman's passion for social reform dovetailed with her passion for one man: Chicago activist, hobo king, and red-light district gynecologist Ben Reitman. This takes us into the heart of their tumultuous love affair, finding that even as Goldman lectured on free love, she confronted her own intense jealousy. As director of the Emma Goldman papers, Falk had access to over 40,000 writings by Goldman--including her private letters and notes--and she draws upon these archives to give us a rare insight into this brilliant, complex woman's thoughts. The result is both a riveting love story and a primer on an exciting, explosive era in American politics and intellectual life
Keywords: Goldman, Emma, -- 1869-1940.